Implicatures and explicatures in English and Spanish commercial messages: pragmatic level versus semantic level - Vivanco, Verónica (Penerbit UKM, 2006)
This article analyses the differences between English and Spanish in technical advertising texts in relation to the concepts of implicature and explicature. It looks at the distinctive features of publicity discourse in both English and Spanish advertising messages. The texts studied show different patterns: fluctuation from implicit to explicit implicatures, explicatures combined with consecutive sentences, explicatures combined with implicatures, and exclusive use of implicatures. The contrast between English and Spanish reveals that the latter makes a full display of implicatures, so that the pragmatic level has a higher level of use. In contrast, English shows a tendency to combine implicatures with explicatures or with consecutive sentences, which also play the role of hidden implicatures. Both the English and Spanish language makes full use of implicatures. They are graded on a scale which ranges from implicit (veiled) to explicit (open) implicatures. The analysis shows that advertising messages share the same behaviour in the self-attribution of the concept of quality; they also show a contrast between the positive features of the company being advertised and insufficiencies of the rival companies; and, finally, this counterbalance is shown by means of the opposition open statements (haves) and implicatures (haves nots).